Fostering Ethics Research: An Analysis of the Accounting, Finance and Marketing Disciplines - Bernardi, Richard A. (Journal of business ethics, 2008)
This study compares the level of ethics research published in 25 business-ethics journals and the Top-40 journals for the accounting, finance, and marketing disciplines. This research documents an increasing level of ethics research in the accounting and marketing disciplines starting in 1992. While the level of finance doctorates reported by the Association to Advance Collegiate Schools of Business (AACSB) has increased at a higher rate (40.4%) than accounting (18.4%) and marketing (32.2%) since 1995, this increase has not been reflected in the level of ethics scholarship in finance. The level of ethics scholarship in finance remained relatively constant between 1987 and 2005 at an average of seven coauthor-adjusted articles per year. However, both the accounting and marketing disciplines now regularly publish approximately 50 coauthor-adjusted articles each year.